2019
DOI: 10.1016/s2468-2667(19)30059-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of maternal mental illness among children and adolescents in the UK between 2005 and 2017: a national retrospective cohort analysis

Abstract: Summary Background Little information exists about the prevalence of children exposed to maternal mental illness. We aimed to estimate the prevalence of children and adolescents exposed to maternal mental illness in the UK between 2005 and 2017 using primary care data. Methods In this national retrospective cohort study, we included children aged 0–16 years born between Jan 1, 1991, and Dec 31, 2015, who were linked to their mothers and registered on the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
121
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(129 citation statements)
references
References 31 publications
(39 reference statements)
6
121
0
2
Order By: Relevance
“…Internationally, rates of maternal mental illness range anywhere from 7.5% in Australia (Buist et al, ) to 38% in the USA (Luciano, Nicholson, & Meara, ). Abel et al () found that Northern Ireland (NI) had the highest levels of maternal mental illness in the UK; with one in four children, aged 0–16 years, exposed to maternal mental illness and 53% of children over 16 having a mother who has been diagnosed with a common (i.e. depression and anxiety) or severe mental illness (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Internationally, rates of maternal mental illness range anywhere from 7.5% in Australia (Buist et al, ) to 38% in the USA (Luciano, Nicholson, & Meara, ). Abel et al () found that Northern Ireland (NI) had the highest levels of maternal mental illness in the UK; with one in four children, aged 0–16 years, exposed to maternal mental illness and 53% of children over 16 having a mother who has been diagnosed with a common (i.e. depression and anxiety) or severe mental illness (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…This is important because mothers are usually the primary caregivers and take a central role in their children's health [9] so the extent to which their children access preventative healthcare is of public health concern. Recently, using presence or absence of maternal mental illness (MMI) from primary care records, we estimated that almost one in four children in the UK has a mother with a mental illness [10] and this number may be growing. These estimates indicate the prevalence of children exposed to different types of MMI in the UK as: non-affective psychosis 0.2%; affective psychosis 0.3%, depression as 18.4%, anxiety as 7.9%; eating disorders 0.1%; personality disorder 0.1% and alcohol and substance misuse as 0.3% [10].…”
Section: Introductionmentioning
confidence: 99%
“…Most research focuses on mothers, ignoring the father's role in the child-rearing environment and most does not account for the multiple adversities CAPRI experience growing up with parental mental illness. 1,2 We do know that these young people experience significant disruption to their lives from repeated parental admission to hospital and illness. The available evidence indicates that the lack of usual parental supports and disruption of family life impairs educational, social and emotional attainment and is associated with behavioural difficulties.…”
Section: Evidence Of Needmentioning
confidence: 99%
“…It paints a precise and comprehensive picture of the phenomenology, psychopathology and harms of gambling. Excerpts from this hymn (from the tenth book of the Rig Veda) are given below; here, a gambler addresses the dice that have destroyed his life and begs them to spare him: 1 'The Gambler:…”
Section: Sanju Georgementioning
confidence: 99%
See 1 more Smart Citation